2016
DOI: 10.1177/1359105316650508
|View full text |Cite
|
Sign up to set email alerts
|

Differential food intake and food choice by depression and body mass index levels following a mood manipulation in a buffet-style setting

Abstract: While eating in response to emotional cues is associated with intake of unhealthy foods, less is known about the extent to which obesity and depression may differentially influence food intake in a buffet-style setting where low- and high-calorie foods are available to choose from. Using a counterbalanced design, 154 participants were grouped by depression and obesity categories, then asked to read a series of vignettes that were sad (on 1 day) and neutral (on a different day), followed by a buffet to eat unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Weight loss is one of the nine specific symptoms of MDD (Sawamura et al, 2016); thus, the animals in this study were weighed weekly to measure how CUMS affected their weights. Some studies have shown an association between depression and food intake (Privitera et al, 2016); therefore, we also recorded the A B C C FIGURE 5 | Effects of chronic unpredictable mild stress (CUMS), Xiaoyaosan, and fluoxetine on the colon tissue mucous membrane appearance and goblet cell morphology. (A) Sections were stained with hematoxylin-eosin staining (H&E) to assess the mucous membrane appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss is one of the nine specific symptoms of MDD (Sawamura et al, 2016); thus, the animals in this study were weighed weekly to measure how CUMS affected their weights. Some studies have shown an association between depression and food intake (Privitera et al, 2016); therefore, we also recorded the A B C C FIGURE 5 | Effects of chronic unpredictable mild stress (CUMS), Xiaoyaosan, and fluoxetine on the colon tissue mucous membrane appearance and goblet cell morphology. (A) Sections were stained with hematoxylin-eosin staining (H&E) to assess the mucous membrane appearance.…”
Section: Discussionmentioning
confidence: 99%
“…For example naturalistic studies that have examined mood related food behaviour during times of increased workload (such as the examination period) found increases in the intake of total energy and fat (McCann, Warnick and Knopp, 1990). In addition, experimental induction of negative mood increased intake of high calorie foods (i.e foods containing a high amount of sugar and fat) in individuals who were depressed (Privitera et al, 2016). In those suffering from affective disorders a lack of adherence to self-care regimens (e.g diet and exercise) exacerbates the associated adverse physiological effects; including reductions in HRV indices (Katon, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, however, to our knowledge no study has investigated the effects of emotions on food choice by using a task similar to ours. The closest to our study is recent work by Privitera et al (2019) which showed that lab-induced negative emotions increased the number of choices of high-caloric food items "in a buffet-style setting." Our null finding regarding a potential relationship between emotions and food choice may stem from the fact that in our study, intake of the chosen items was less immediate than in the study by Privitera et al (2019): Our choice environment more resembled choice in a supermarket than a "buffet-style" choice.…”
Section: A B Cmentioning
confidence: 79%